(untitled) (CIPEEX, 2022)
FESCAN’S CEJUSC IS A NEUTRAL ENVIRONMENT THAT OFFERS THE COMMUNITY FREE ACCESS TO JUSTICE. ON THE OTHER HAND, IT PROVIDES THE STUDENTS WITH A STRUCTURE, EQUIVALENT TO A JUDICIAL UNIT, THAT IS, THE OPPORTUNITY TO SOLVE A CONFLICT IN A CONSENSUAL MANNER, WITHOUT ALL THE JUDICIAL APPARATUS INVOLVED. THE "RAPPORT" TECHNIQUE, OR "ACTIVE LISTENING", IS PART OF THE PSYCHOLOGY AREA, USED TO CREATE A CONNECTION, A COMMUNICATION BETWEEN THE PARTIES. THUS, THE MEDIATOR/CONCILIATOR/ADVOCATE STRATEGICALLY USES THE "RAPPORT" TECHNIQUE TO BUILD CREDIBILITY BETWEEN THE PARTIES TO RESOLVE THE CONFLICT. THIS PAPER AIMS TO ANALYZE THE CONTRIBUTIONS OF THE "RAPPORT" TECHNIQUE DURING THE HEARINGS HELD AT THE CONFLICT RESOLUTION JUDICIARY CENTER (CEJUSC) OF THE EVANGELICAL COLLEGE OF SENADOR CANEDO. WE INTEND TO UNDERSTAND THE IMPORTANCE OF THE CEJUSC THROUGH A QUANTITATIVE RESEARCH, THAT IS, WE WILL ANALYZE IF THE USE OF THE "RAPPORT" TECHNIQUE IN THE HEARINGS AND SELF-COMPOSITIVE SESSIONS COLLABORATED IN THE RESOLUTION OF THE PROBLEMS PRESENTED BY THE COMMUNITY. HOWEVER, TO OBTAIN THE BEST SOLUTION TO THE PROBLEM PRESENTED, IT IS NECESSARY TO APPLY TECHNIQUES TO BRING THE PARTIES TOGETHER. FINALLY, THIS PAPER AIMS TO DEMONSTRATE THAT THE "RAPPORT" TECHNIQUE IS NECESSARY FOR THE CEJUSC, WHICH IS AN IMPORTANT INSTANCE TO SOLVE A CONFLICT THAT CAN BE MEDIATED OR CONCILIATED, EVEN BEFORE IT IS TAKEN TO THE JUDICIARY.